Basic electro-optics for electrical engineers - Boreman, G. D. (Tutorial texts in optical engineering ;, 1998)
This text introduces imaging, radiometry, sources, detectors, and lasers, with special emphasis on flux-transfer issues. The first-order approach enables students to make back-of-the-envelope calculations needed for initial setup of optical apparatus. It is intended for students and newcomers to electro-optics.